РАЗВИТИЕ ТЕЛЕКОММУНИКАЦИЙ ПРАО АКЦ ФИАН - Исаев, Е. А.; Думский, Д. В.; Лихачев, С. Ф.; Шацкая, М. В.; Пугачев, В. Д.; Самодуров, В. А. (Одеські астрономічні публікації, 2011)
The new modern and reliable data storage system was acquired in 2010 in order to develop internal telecommunication resources of the Observatory. The system is designed for store large amounts of observation data obtained from the three radio-astronomy complexes (PT-22, DKR-1000 and BSA). The digital switching system - "Elcom" is installed in the Pushchino Radio Astronomy Observatory to ensure the observatory by phone communications. The phone communication between buildings of the observatory carried out over fiber-optic data links by using the ip-telephony. The direct optical channel from tracking station RT-22 in Pushchino to Moscow processing center has been created and put into operation to transfer large amounts of data at the final stage of the establishment of ground infrastructure for the international space project "Radioastron". A separate backup system for processing and storing data is organized in Pushchino Radio Astronomy Observatory to eliminate data loss during communication sessions with the Space Telescope.